MicroRNA-638 inhibits cell growth and tubule formation by suppressing VEGFA expression in human Ewing sarcoma cells. Issue 1 (19th January 2018) - Zhou, Xin; Chen, Jiajun; Xiao, Qianren; Wang, Tengyu; Yu, Yu; Li, Bo; Shao, Gaohai; Li, Yunyun; Zhang, Zhongzu
Abstract : Ewing sarcoma (EWS) is a kind of aggressive tumor of bone and soft tissues, which most occurring in children and adolescents. MicroRNAs (miRNAs) perform essential function in the progression and development of EWS, while the putative role of miR-638 in EWS remains uncertain. Accordingly, we detected the expression of miR-638 and explored its putative biological effects on the malignant phenotype of EWS cells. As expected, miR-638 was significantly down-regulated in EWS cells. Moreover, overexpression of miR-638 suppressed cell growth, induced cell apoptosis, and inhibited tubule formation of EWS cells in vitro . Among the putative target genes of miR-638 predicted by the miRNA target prediction tools, vascular endothelial cell growth factor A (VEGFA) attracted out attention most. The luciferase reporter assays reaffirmed that VEGFA was a targeted gene of miR-638 in EWS cells. Furthermore, miR-638 suppressed the mRNA and protein level of VEGFA, and restored the expression of VEGFA reversed the suppressed effects of miR-638 in EWS cells. Taken together, the results suggested that miR-638 might perform tumor suppressive effects in EWS, which might be mediated, at least partially, through suppressing the activity of VEGFA.